Mathematics
GeorgianaLaura96
20

Solve for Substitution: x = 3y - 7 3x + y = -1

+2
(2) Answers
FLEXUSEXTREMEIN

4x-2y=-8x = 4y = 4................................................

Mase408

Plug (3y-7) into the second equation as x. 3(3y-7)+y=-1 Now solve it like a regular equation! First, distribute the 3 into (3y-7) 9y-21+y=-1 Combine the like terms 10y-21=-1 Now, add 21 to both sides of the equation. 10y=20 Finally, divide each side by 10. y=2 Plug 2 into the first equation as y. x=3(2)-7 x=6-7 x=-1 To check your answer, plug x and y into the second equation. 3(-1)+2=-1 -3+2=-1 -1=-1 x=-1 y=2 Hope this helped! :)

Add answer